Coworkers, Networks, and Job Search Outcomes - Perihan Ozge Saygin; Andrea Weber; Michèle A. Weynandt (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
Social networks are an important channel of information transmission in the labor market. This paper studies the mechanisms by which social networks have an impact on labor market outcomes of displaced workers. We base our analysis on administrative records for the universe of private sector employment in Austria where we define work-related networks formed by past coworkers. To distinguish between mechanisms of information transmission, we adopt two different network perspectives. From the job-seeker's perspective we analyze how network characteristics affect job finding rates and wages in the new jobs. Then we switch to the perspective of the hiring firm and analyze which types of displaced workers get hired by firms that are connected to a closing firm via past coworker links. Our results indicate that employment status and the firm types of former coworkers are crucial for the job finding success of their displaced contacts. Moreover, 21% of displaced workers find a new job in a firm that is connected to their former workplace. Among all workers that were displaced from the same closing firm those with a direct link to a former coworker are twice as likely to be hired by the connected firm than workers without a link. These results highlight the role of work related networks in the transmission of job information and strongly suggest that job referrals are an important mechanism.
Keywords: J63; J64; M51; 330; Social Networks; Job Displacement; Plant Closure; Referral Hiring